Median time to pain improvement and the impact of baseline pain severity on pain response in patients with psoriatic arthritis treated with tofacitinib. Issue 2 (5th July 2021) - de Vlam, Kurt; Ogdie, Alexis; Bushmakin, Andrew G; Cappelleri, Joseph C; Fleischmann, Roy; Taylor, Peter C; Azevedo, Valderilio; Fallon, Lara; Woolcott, John; Mease, Philip J
Abstract : Background: Pain is a core domain of psoriatic arthritis (PsA). This post hoc analysis evaluated time to pain improvement and the impact of baseline pain severity on pain response in patients with PsA receiving tofacitinib. Methods: Data from two trials (NCT01877668 ; NCT01882439 ) in patients receiving tofacitinib 5 mg twice daily, placebo switching to tofacitinib 5 mg twice daily at month 3 (placebo-to-tofacitinib) or adalimumab (NCT01877668 only) were included. Improvement in pain (≥30%/≥50% decrease from baseline in Visual Analogue Scale pain score) was assessed; median time to initial (first post-baseline visit)/continued (first two consecutive post-baseline visits) pain improvement was estimated (Kaplan-Meier) for all treatment arms. A parametric model was used to determine the relationship between baseline pain severity and time to pain response in patients receiving tofacitinib. Results: At month 3, more patients experienced pain improvements with tofacitinib/adalimumab versus placebo. Median days (95% CI) to initial/continued pain improvements of ≥30% and ≥50%, respectively, were 55 (29–57)/60 (57–85) and 85 (57–92)/171 (90–not estimable (NE)) for tofacitinib, versus 106 (64–115)/126 (113–173) and 169 (120–189)/NE (247–NE) for placebo-to-tofacitinib. Pain improvements were also experienced more quickly for adalimumab versus placebo. Predicted time to ≥30%/≥50% pain improvement was shorter in patients with higher baseline pain versus lower baseline pain (tofacitinib arm only). Conclusions: In patients with PsA, pain improvements were experienced by more patients, and more rapidly, with tofacitinib and adalimumab versus placebo. In those receiving tofacitinib, higher baseline pain was associated with faster pain improvements.